Travel time and distance to health care only partially account for the ethnic inequalities in cervical cancer stage at diagnosis and mortality in New Zealand - Naomi Brewer; Neil Pearce; Peter Day; Barry Borman (Elsevier, 2012)
Abstract Objective: To investigate whether travel time or distance to the nearest general practitioner (GP) and/or cancer centre accounts for the ethnic differences in cervical cancer screening, stage at diagnosis and mortality in New Zealand (NZ). Methods: The study involved 1,594 cervical cancer cases registered between 1994 and 2005. Travel time and distance to the GP and cancer centre were estimated using a Geographical Information System. Results: Adjustment for travel time or distance made almost no difference to ethnic differences in screening rates. Adjustment for travel time reduced the excess risk for late‐stage diagnosis in Māori (the odds ratio (OR) reduced from 2.71 (95%CI 1.98-3.72) to 2.59 (1.88-3.56), a 7% decrease) and 33% in Pacific (the OR reduced from 1.39 (0.76-2.54) to 1.26 (0.68-2.33)) women. Adjustment for travel time reduced the excess risk for mortality by 3% in Māori (the hazard ratio (HR) reduced from 1.59 (1.21-2.08) to 1.57 (1.19-2.06)) and 13% in Pacific (the HR reduced from 1.92 (1.20-3.08) to 1.80 (1.11-2.91)) women. Similar findings were observed when using travel distance rather than travel time. Conclusions: Travel time and distance are only weakly associated with cervical cancer screening, stage at diagnosis and mortality in NZ. However, travel time may account for a small proportion of the ethnic differences in stage at diagnosis, and to a lesser extent mortality, particularly for Pacific women. Implications: The findings suggest that there may be ethnic variations in access to treatment or treatment quality, which may be related to travel time.